MORAL VALUES INTERNALIZATION THROUGH PROBLEM-BASED LEARNING - Nursyamsiah, Nunung (International Journal of Education, 2014)
This study investigates and analyzes learning phenomena related to moral values in the contextof problem-based learning activities, the process of moral values internalization in relation toproblem-based learning situations, conditions that relate to the enhancement of comprehensionas well as internalization of the values, and their impact to the tendency of actualizing thevalues into better student behaviour. This research was conducted with participation of thestudents of the Arabic Department, Faculty of Language and Arts Education, IndonesiaUniversity of Education in the academic years 2009, 2010, and 2011. The data to be analysedin this research comprises of the students’ written responses (initial responses, group workresponses, and written reflection), classroom observation, and in-depth interviews. The dataused was analyzed by considering the principles of credibility, dependability, transferability,and confirmability. Data analysis, using principles of qualitative approach, reveals phenomenarelating to the students’ comprehension, feelings, and behavior regarding the moral values, as aresult of learning stages designed based on the theoretical framework. In addition to this result,an instructional theory and a learning theory can be formulated.Key words: internalization, akhlak (moral) values, problem-based learning